A novel pythagorean fuzzy entropy measure using MCDM application in preference of the advertising company with TOPSIS approach. (2023) - Kumar, Ravinder; Gandotra, Neeraj; Suman,
Abstract: The various extensions of the fuzzy set are considerably applied in many complex problems of real world to describes the improper information. The PFS (pythagorean fuzzy set) which is the expanded form of IFS (intuitionistic fuzzy set) is more applicable and precise to measure the uncertainty. The research work presents the novel entropy measure defined on PFS which satisfied axioms of the entropy. The entropy measure is determined the uncertainty that defined the fuzziness degree on the fuzzy set. The applicability of the entropy is verified in selection of the advertising company and results compared to the existing entropies defined on PFS. The outcomes of the illustrative example show that the new entropy measure is more precise, simpler, and consistent as compare to existing entropies on PFS.